Proximate values and elemental analysis in wheat and soybean using inductively coupled plasma mass spectrometry - G. Kowmudi; V. Rashmi; K. Anoop; N. Krishnaveni; S. Naveen (Global Journal of Environmental Science and Management)
BACKGROUND AND OBJECTIVES: Determining food composition and bioactivity is critical to both theoretical and applied research in food science and technology. This is frequently used to determine the nutritional value and overall acceptance of the food by consumers. The current study's goal is to determine the macronutrient, mineral and antioxidant activity of selected wheat and soybean varieties with the potential to be useful in the food industry to develop value-added products that are safe for consumption.METHODS: The proximate and mineral composition, gluten characterization, total phenolic contents, and antioxidant activity of three wheat cultivars  and five soybean cultivars that are indigenous to India were studied.FINDINGS: Wheat varieties were found to be rich in carbohydrates (65.8-68.8 percent) and gluten (27.2-28.6 percent), whereas soybean varieties were found to be the richest source of protein (32.8-33.7 percent), fat (17.1-17.6 percent), fiber (21.7-28.8 percent), polyphenols (2.76-3.59 milligram gallic acid equivalent per gram, and antioxidant activity (97-123 microgram ascorbic acid equivalent per gram). These samples were also found to have significant content of essential minerals.CONCLUSION: The tested samples had a high nutritional value and energy content and could be a good source of nutrition for a large population. A comprehensive report on the proximate and mineral composition, total phenolic content and antioxidant activity of the wheat and soybean varieties collected from the Rewa district, India, was reported.